Description Of The Implementation Of The Simultaneous Measurement And Intervention Program For Stunting Management In The Banguntapan III Public Health Center Area - Imansari, Lutfi; Sunarti, Sunarti; Suryani, Dyah (Sean Institute, 2024)
Stunting was a chronic nutritional problem that affected the growth and development of children in Indonesia. The prevalence of stunting in Indonesia decreased from 24.4% in 2021 to 21.6% in 2022. However, this figure was still above the national target of 14%. The government implemented the Simultaneous Measurement and Intervention Movement to Prevent Stunting program to accelerate the reduction of stunting. This research aimed to describe the implementation of the Simultaneous Measurement and Intervention Program for Stunting Management in the Banguntapan III Public Health Center area. This study used a qualitative descriptive method with research subjects that included the Stunting Reduction Acceleration Team, cadres, health teams, pregnant women, children aged 0-59 months, and prospective brides in the Banguntapan III Public Health Center working area. Data were collected through participatory observation and documentation, and analyzed narratively. The results showed that the implementation of the Simultaneous Measurement and Intervention Program for Stunting Management in the Banguntapan III Public Health Center had been optimal but required improvements in several areas. Despite good coordination, the target number achieved was only 99.12%. Data showed an increase in stunting cases after the program. In April, there were 24 cases of